The Paradigm of Islamic Religious Education in the Perspective of Religious Moderation and National Resilience: The Integrative-Transformative Model of Moderate Resilience (MITKM) - Bakhri, Alim; Saleh, Maratun (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Islamic Religious Education (PAI) in Indonesia faces multidimensional challenges in the era of digital disruption and social polarization, which include radicalism based on textual interpretation, identity politics, fragmentation of digital religious authority, and low critical religious literacy among the younger generation. This phenomenon is reinforced by global and national trends, including the spread of extremist content thru social media, exclusive identity claims, and weak social cohesion among teenagers (PPIM UIN Jakarta, 2021; Hidayat, 2022; Wahid Foundation, 2022). This research aims to formulate a new paradigm of Islamic Religious Education (PAI) based on religious moderation that is not only normative-theological but also strategic in strengthening national resilience. This research uses a qualitative approach with a literature study method, thru philosophical-critical and comparative analysis of contemporary literature relevant to the research theme. The study results indicate that Islamic Religious Education (PAI) needs to be reconstructed thru the Integrative-Transformative Model of Moderate Resilience (MITKM), which integrates epistemological, affective-identity, and transformational-social dimensions. This model fosters religious critical literacy, internalization of moderate religious values, awareness of pluralism, love for the homeland, and ideological immunity against extremist narratives and digital propaganda. The integration of moderate religious values into the curriculum, dialogical-critical pedagogy, and reflective evaluation has the potential to strengthen social cohesion, cultivate empathy across identities, and enhance the nation's ideological resilience. Thus, MITKM offers conceptual and applicative contributions to PAI as a strategic instrument for character development, the formation of religious-national identity, and the strengthening of national resilience amidst the challenges of digital disruption and social complexity. Keywords: Islamic Religious Education, Religious Moderation, National Resilience, Ideological Immunity, Educational Transformation.